Acute phenytoin intoxication in a 4-year-old mimicking viral meningoencephalitis. (25th June 2013) - Shukla, Amlin; Sankar, Jhuma; Verma, Ankit; Dubey, Nandkishore
Abstract : We report here the case of a 4-year-old female preschooler who presented to the emergency department with generalised tonic-clonic convulsions and history of vomiting, irritability and dysarthria of short duration. On examination she was found to be responsive only to painful stimulus, had terminal neck stiffness and bilateral extensor plantars. In view of her clinical presentation, an initial diagnosis of viral meningoencephalitis was made in the emergency room and the child treated accordingly. On subsequent transfer to the intensive care unit (ICU), the parents revealed additional history of an elder sibling taking phenytoin for seizures. Therefore, a suspicion of acute phenytoin toxicity was made and phenytoin levels sent for confirmation. Her serum phenytoin level was 80 μgm/mL (normal: 10–20). The child was managed conservatively and discharged after 5 days of hospitalisation. We chose to report this case to highlight the unusual presentation of this rare intoxication.